Heart rate variability in dorper sheep in the fetal and neonatal periods until 120 days of age: Use of the technique in the field - Cruz-Aleixo, Amanda Sarita [UNESP]; De CASTRO FERREIRA LIMA, Mayra [UNESP]; HOLANDA DE ALBUQUERQUE, Ana Luísa [UNESP]; Tortorelli Teixeira, Raphael [UNESP]; ALVES DE PAULA, Renata [UNESP]; Grandi, Marina Cecília; Laurenti Ferreira, Danilo Otávio; Harumi Tsunemi, Miriam [UNESP]; Biagio Chiacchio, Simone [UNESP]; Gomes Lourenço, Maria Lucia [UNESP] (Japanese Society of Veterinary Science, 2021)
The evaluation of the autonomic cardiac functions may be performed through the analysis of the heart rate variability. Heart rate variability is defined as the fluctuations in the heart rhythm or rate, and represents a useful tool in the evaluation of the autonomic nervous system through the sympathetic and parasympathetic components, as well as its balance and its reflexes on the cardiorespiratory control system. Fetal electrocardiography provides important information regarding the well-being of the fetus since, in human fetuses, there are changes in the behavior of the fetal heart rate during the second and third trimesters of pregnancy due to an increase in parasympathetic activity. Therefore, considering the importance of evaluating fetal viability, this study aims at evaluating the behavior of fetal heart rate and heart rate variability in Dorper sheep, as well as the activity of the autonomic nervous system during fetal life and in newborn lambs. The species is often used in experimental studies and autonomic nervous system activity is a prognostic index, therefore, the diagnosis of modifications in the sympathovagal balance may represent an early index for fetal viability and well-being in lambs. The analyses were performed in 10 Dorper sheep during pregnancy and in 10 lambs after birth until 120 days of age. There was a decrease in the fetal heart rate and heart rate variability indexes during the fifth month of pregnancy, but without statistical significance for the period evaluated. The heart rate of the lambs decreased gradually until they were 21 days old. The indexes SDNN (standard deviation of RR intervals) and RMSSD (square root of the mean of successive differences between adjacent RR intervals) diverged according to age, being high at day 60. Fetal viability is relevant in sheep fetuses to avoid losses during pregnancy and risks to the health of the mother. In the species, there seems to be a predominance of parasympathetic activity starting from the 21st day of age. Heart rate variability may be employed as a tool in the evaluation of the fetus and development of lambs, since changes in its behavior may represent an adverse effect to fetal and neonatal health.
Keywords: Autonomic nervous system; Fetus; Heart rate; Pregnancy sheep